Fenomena Self-Injury pada Remaja - Yurike Delyaputri; Cherryna Gumay Vara; Salsabila Patrisia; Difani Nurhafizha; Risma Anita Puriani; Rizki Novirson (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Adolescence is a challenging transition phase, where the inability to manage emotional distress can lead to self-injury behavior, which is self-injury without suicidal intent. This behavior is influenced by internal factors, such as automatic negative thoughts, as well as external factors, such as peer pressure and social media exposure. This research uses a qualitative method with a literature study approach, analyzing 23 national journals indexed by SINTA and GARUDA within the last 10 years. The results of the analysis show that self-injury is often used by adolescents as a coping strategy to relieve negative emotions, such as anger, sadness, or frustration. Triggering factors include difficulty managing emotions, traumatic experiences, lack of social support, and influence from the environment and media. The impact of self-injury is serious, including disruptions in learning, difficulty solving problems, decreased self-esteem, and an increased risk of suicide attempts. A proven effective intervention is cognitive-behavioral therapy, which needs to be adapted to the social and cultural context of adolescents. This study provides insights for mental health professionals and educators to design appropriate, adaptive, and sustainable interventions to address adolescent self-injury behavior.